2014
DOI: 10.7763/ijcee.2014.v6.795
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Inlet Velocity Profiles on the Prediction of Velocity Distribution inside an Electrostatic Precipitator (ESP)

Abstract: Abstract-In this study, the development of CFD model for the description of operation of electrostatic precipitator has been developed. The model is based on the simulation analysis whereby focused on the gas flow by time-averaged conservation equation of mass and momentum. 2D geometry model was extensively applied due to ease the geometry and analysis. The flow simulation was performed by using computational fluid dynamics (CFD) code Fluent. Numerical calculations for the air flow were calculated using the Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Authors have found that local eddy downstream of the plate is the main cause of pressure loss. Effects of air inlet velocity magnitude on the velocity distribution in ESP was investigated by Yusop et al [15]. Again, a 2D CFD model was used in their investigations.…”
Section: Previous Studies Of Modelling Of Flow Through Perforated Platesmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors have found that local eddy downstream of the plate is the main cause of pressure loss. Effects of air inlet velocity magnitude on the velocity distribution in ESP was investigated by Yusop et al [15]. Again, a 2D CFD model was used in their investigations.…”
Section: Previous Studies Of Modelling Of Flow Through Perforated Platesmentioning
confidence: 99%
“…The above assumptions are commonly applied for modelling of flow distribution systems for ESP [3,8,15,19]. The turbulence model k-ω was applied for the discussed case of flow distributor [22].…”
Section: Single Plate Modellingmentioning
confidence: 99%